Palivizumab Prophylaxis: Does It Have Any Influence on the Growth and Development of the Infants? - Tavsu, Ismail; Gursoy, Tugba; Dirman, Sukriye; Erbil, Nazan; Ovali, Fahri (American Journal of Perinatology, 2014)
Aim To evaluate the rehospitalization rates of premature infants who received palivizumab prophylaxis and its influence on the growth and development of these infants.Methods Infants with a gestational age of less than 32 weeks were randomized to receive prophylaxis with palivizumab (study group) or nothing (control group). Nasal swab samples were obtained monthly in all cases and also in case of infection and hospitalization. At the corrected age of 18 months Guide for Monitoring Child Development (GMCD) was administered to all patients and anthropometric indices were evaluated.Results The study was completed with 39 infants in the study group and 40 infants in the control group. Incidence of hospitalization due to respiratory syncitial virus (RSV) was found to be significantly lower in the study group both at the year of prophylaxis and in the following year (p = 0.001, odds ratio 1.32 [1.11–1.57]). There were no significant differences in terms of anthropometric indices or GMCD tests between the groups at the corrected age of 18 months.Conclusion Palivizumab reduced the incidence of lower respiratory tract infections and hospitalizations due to RSV both in the year of prophylaxis and in the following year. However, this decrease did not have any impact on the development of infants.
Keywords: palivizumab; respiratory syncitial virus; rehospitalization; neurodevelopment; growth